(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is the leading chronic liver disease worldwide. Early diagnosis is crucial to manage NAFLD timely. This study was aimed to evaluate the changes in hepatic enzymes in patients with NAFLD and determine the relation of hepatic enzymes with obesity and lipid profile. Materials and methods: This descriptive cross-sectional study was conducted in the Department of Physiology in Chittagong Medical College Hospital from June 2016 to September 2016. Seventy-five subjects with NAFLD on ultrasonography were included from the Department of Radiology of Chittagong Medical College Hospital. Participants were subjected to anthropometric and clinical examinations. Liver enzymes- Serum Alanine aminotransferase (ALT) Aspartate Aminotransferase (AST) were estimated according to the standard guideline. Results: Liver enzyme ALT and AST were elevated respectively in 68% and 44% of the NAFLD patients. Mean values were also higher than the normal referral range. Both ALT and AST were significantly higher in older patients with higher BMI (³25 kg/m 2 ) in patients with high cholesterol, Triglyceride (TG) and Low- Density Lipoprotein (LDL) (p<0.05). Both ALT and AST level showed a significant positive correlation with serum cholesterol, TG and LDL but only serum ALT showed a strong positive correlation with BMI. Conclusion: The study suggested that liver enzyme levels alter in NAFLD patients and also highlighted the importance of age, BMI, and dyslipidemia to assess individuals risk for NAFLD, which reaffirms the connection to the disease. JCMCTA 2024 ; 35 (2) : 95-99